Stormwater Drainage Design (Case Study: UTHM Campus) - Ibrahim, Rabiatul Najwa; Ahmad, Noor Aliza (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
The impervious surface has risen as a result of development is growing rapidly. Impervious surfaces are considered to have poor water permeability as the surface prevents water from penetrating it which can lead to increased surface runoff. The rise of surface runoff at impervious area such as paved road and parking area will be far more severe especially when there is no existing drain nearby at Jalan Kolej in UTHM Campus. Along with the condition of road chambers that have slope to drain surface runoff to the road shoulder also may increase the surface runoff drastically in that area as the water will accumulate more due to slow infiltration rate. Therefore, the objective of this case study is to determine runoff problem at impervious area that may cause flash flood as well as to propose a good design for new storm water drainage. In this study, the rational method and Manning’s equation were applied. Rational method was used to determine the peak runoff in the study area and Manning’s equation was used to ensure that the stormwater drain designed were able to accommodate peak surface runoff. As a result, it was discovered that the poor infiltration rate in the study area was also a contributing factor to increasing impervious surface runoff. The lowest infiltration rate discovered in UTHM Campus was 9.78 mm/hr. In order to decreased surface runoff on impervious surfaces while minimising the risk of flash floods, the designed stormwater drain should be able to accommodate peak flow. The peak discharge at the study area was at subcatchment 3 with 1.723 m3/s while the designed stormwater drainage capacity was 4.119 m3/s. By doing this study, runoff problems were identified and a stormwater drain was developed to mitigate the problem in the study area.